The SEIR model incorporating asymptomatic cases, behavioral measures, and lockdowns: Lesson learned from the COVID-19 flow in Sweden. (March 2023) - Khairulbahri, Muhamad
Abstract: The Sweden approach is unique in handling the COVID-19 flow, compared to other European countries. While other countries have practiced the full lockdowns, Sweden has practiced the lighter lockdowns or the partial lockdowns as public spaces such as cafes and restaurants are allowed to serve their customers subject to government recommendations. This study aims to develop an SEIR model for Sweden capturing important issues such as the roles of behavioral measures, partial lockdowns, and undocumented cases. The suggested SEIR model is probably the first SEIR model capturing the roles of behavioral measures, partial lockdowns, hospital preparedness, and asymptomatic cases for Sweden. The SEIR model can successfully reproduce similar main observed outputs, namely documented infected cases and documented death cases. This study finds that the effects of partial lockdowns effectively start 52 days after the first confirmed case. Again, behavioral measures and partial lockdowns reduce possible infected cases about 22% and 70% respectively. This study also suggests that the Sweden government should step up to the full lockdowns by conducting public closures so COVID-19 flow can be curtailed significantly. Likewise, owing to airborne transmission, protecting vulnerable people such as senior citizens should be prioritised.